Straight outta Deadwood - Boop, David (Baen, 2020)
Once again, we return to the Old West with a new posse of top authors spin tales of horror, fantasy, and science fiction. We take no prisoners as they explore what really was, and mix in what might have been. Charlaine Harris...shows us a glimpse inside her new series as a tormented gunfighter faces a true demon of her past. Mike Resnick... reveals what Doc Holiday thought was so funny on his last day. Jeffrey Mariotte... introduces us to a man who specializes in pictures of the dead who won't stay dead. Jane Lindskold ... teaches us not to underestimate a schoolmarm when her students are in jeopardy. And Shane Hensley ... cooks up a stew that threatens to send every famous lawman in history to their graves! Plus, a dozen more stories of how the west was wilder than any history book could contain, such as a new Native American legend by Stephen Graham Jones and a Mormon troubleshooter straddling the line between his faith and the supernatural by D.J. Butler.